2014
DOI: 10.1155/2014/364316
|View full text |Cite
|
Sign up to set email alerts
|

Deregulation of Serum MicroRNA Expression Is Associated with Cigarette Smoking and Lung Cancer

Abstract: Lung cancer is the leading cause of cancer-related death and cigarette smoking is the main risk factor for lung cancer. Circulating microRNAs (miRNAs) are considered potential biomarkers of various cancers, including lung cancer. However, it is unclear whether changes in circulating miRNAs are associated with smoking and smoking-related lung cancer. In this study, we determined the serum miRNA profiles of 10 nonsmokers, 10 smokers, and 10 lung-cancer patients with miRCURY LNA microRNA arrays. The differentiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 45 publications
2
58
0
Order By: Relevance
“…Indersie et al reported that let‐71‐3p, miR‐449b‐3p, and miR‐885‐5p were decreased in tumors compared to normal livers, and that these miRNAs inhibited HBL cell grow and Wnt signaling activity in vitro, partly through beta‐catenin downregulation . Some studies predicted the potential target genes of let‐7i‐3p and its involvement in various cellular pathways . It was shown that these target genes such as CXCR6 and CXCL12, which play roles in leukocyte transmigration, are key molecule candidates in KD .…”
Section: Discussionmentioning
confidence: 99%
“…Indersie et al reported that let‐71‐3p, miR‐449b‐3p, and miR‐885‐5p were decreased in tumors compared to normal livers, and that these miRNAs inhibited HBL cell grow and Wnt signaling activity in vitro, partly through beta‐catenin downregulation . Some studies predicted the potential target genes of let‐7i‐3p and its involvement in various cellular pathways . It was shown that these target genes such as CXCR6 and CXCL12, which play roles in leukocyte transmigration, are key molecule candidates in KD .…”
Section: Discussionmentioning
confidence: 99%
“…Circulating levels of miR‐939 were used to differentiate between cirrhotic patients with or without hepatocellular carcinoma . MiR‐154 was reduced in the serum of smokers and lung cancer patients relative to non‐smoking healthy individuals . Serum miR‐142‐3p was reduced in patients with colorectal carcinoma .…”
Section: Discussionmentioning
confidence: 99%
“…59 MiR-154 was reduced in the serum of smokers and lung cancer patients relative to non-smoking healthy individuals. 60 Serum miR-142-3p was reduced in patients with colorectal carcinoma. 61 These observations suggest that the detection of a combination of multiple miRNAs is needed to improve the detection and clinical outcomes of endometriosis in relation to other diseases.…”
Section: Potential Biomarkersmentioning
confidence: 98%
“…Several studies have reported that acute physical activity and prolonged exercise training programmes can modify the circulating miRNA profile [87]. Furthermore, smoking appears to alter the pattern of circulating miRNAs [88][89][90][91], and of the miRNAs affected, miR-29b was identified to be deregulated in diabetic patients [27,28,70]. Environmental exposure to air pollutants and chemicals seems to modify circulating miRNAs [92], inducing a bias that is difficult to estimate.…”
Section: Current Limits To the Use Of Circulating Mirnas In Clinical mentioning
confidence: 99%